Phosphorus and Silicon Modified Alginate as an Efficient Flame Retardant for Poly(lactic acid) - Kata Enikő Decsov; Viktória Cserni; Beáta Szolnoki; Olga Krafcsik; Katalin Bocz (Macromolecular Materials and Engineering, 2024)
Abstract The introduction of biobased carbon sources in intumescent flame retardant formulations is extensively explored, particularly for biopolymers such as poly(lactic acid) (PLA). In this work, the flame retardant efficiency of alginate, a favorable renewable charring agent candidate, is enhanced by chemical modification with a phosphorus‐ and silicon‐containing compound and subsequent coagulation in the presence of Ca2+ ions. The simultaneous presence of P and Si atoms in the reactive compound is shown to be an effective way to avoid thermal stability issues related to the biobased carbohydrate. The newly synthesized PSilAlg additive boosts the flame‐retardant effectiveness of ammonium‐polyphosphate (APP) at low loadings. Adding 5 wt% PSilAlg to 15 wt% APP containing PLA composite increases the limiting oxygen index from 26.0 to 34.0 vol% and decreases the total heat emission during combustion by 46%, accompanied by significantly (by 66%) reduced smoke production. The outstanding flame retardant performance of PSilAlg is attributed to the high amount and thermally stable carbonaceous fire‐protecting layer that forms as a result of the enhanced charring, catalyzed by the high oxidation state P, and the strengthening mechanism of inorganic silicates and calcium salts.